Mapping the Literature on Sustainability Reporting: A Bibliometric Analysis Grounded in Scopus and Web of Science Core Collection - Pasko, Oleh; Chen, Fuli; Oriekhova, Alvina; Brychko, Alina; Shalyhina, Iryna (European Journal of Sustainable Development, 2021)
Sustainability reporting has become an increasingly common practice among companies around the globe as around 90% of the world’s 250 largest companies from Fortune 500 prepare and publish its sustainability reporting. Aiming to help researchers to grasp the intellectual landscape of global research on sustainable reporting, we conducted a bibliometric analysis using CiteSpace software by applying evaluative and relational techniques to 928 articles published in 480 different journals in Scopus and 698 articles published in 374 different journals in Web of Science Core Collection from 1981 to 2020. Our findings indicate that the number of articles published in the field has increased rapidly, especially since 2009. We identified the leading countries (the United States, Australia, the United Kingdom, Germany, Spain, Canada, the Netherlands and Italy), the most prolific journals (Journal of Cleaner Production, Business Strategy and the Environment, Journal of Business Ethics), main journals categories (Business, Economics, Management and Finance, Environmental and Ecology and Science, Technology and Engineering), and the major research directions in the near future (sustainability reporting, corporate social responsibility, sustainable development, disclosure). From our findings we infer that the sustainability reporting research has just recently (2013-2019) gained traction in the literature. Moreover, our findings testify that a kind of bifurcation point has occurred is 2011 that manifests the maturity of the field of sustainability reporting. All this provides the reader with a high-view look at sustainable reporting as these quantitative findings complementing qualitative and providing valuable insights into the field.